Differentiated Integration Beyond Brexit Revisiting Cleavage Perspective in Times of Multiple Crises - Radunz, Alexander (Routledge Research in Comparative Politics, 2024)
political conflict; Germany; European integration differentiation; differentiation; differentiated integration; party responses; Poland; United Kingdom; Switzerland